Biological and Health Impact of Astaxanthin Powders in Common Carp Cyprinus carpio L. - Avan Aladin Sadraddin; Bakhan Rafiq Hassan; Shaima Saleh Mahmood; Nasreen MohiAlddin; Raber Mahmud Rashid; Karzan Namiq (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2019)
The effect of astaxanthin powders on biological, health and growth parameter of common carp Cyprinus carpio L. Fish weight varied between (59.2 –66.4gm)were studied for 10 weeks. four treatments(three replicates/treatment) were employed as follows: T1: Diet without any addition, T2: adding 2.5 gm astaxanthin powders / kg diet, T3: adding 5 gm astaxanthin powders / kg diet, T4: adding 7.5gm astaxanthin powders / kg diet. Twice daily feeding at 9:00 a.m. and 2:00 p.m. should be considered that the feeding rate of biomass weight after each took biometrics. Finally, blood samples were taken from the caudal vein of fish. The results showed no significant difference between treatments in terms of biological parameter (p>0.05). The results showed significant difference between treatments in terms of body indices, including Gonadosomatic, but no significant difference (p>0.05) Hepatosomatic, Spleenosomaticindex and Gill index. The results showed a significant difference between treatments in terms of growth performance (p<0.05), including weight gain, Relative growth rate and Specific growth rate. Group results of blood factors showed that between Granulocytes, Lymphocytes and Monocytes there was no significant difference between treatments (p>0.05). Lastly, we found that diets containing higher levels of Astaxanthin powders improve the growth performance, biological and GSI in common carp Cyprinus carpio L.